Levels of metalloproteinases and adipose tissue hormones in men with coronary atherosclerosis - Ya. V. Polonskaya; E. V. Kashtanova; E. M. Stakhneva; S. R. Ledovskikh; E. V. Garbuzova; V. S. Shramko; A. V. Kurguzov; I. S. Murashov; E. V. Sadovsky; Yu. I. Ragino (Бюллетень сибирской медицины)
Aim. To study the effect of adipose tissue hormones on the level of metalloproteinases in men with verified coronary atherosclerosis and to assess associations between the studied biomarkers and abdominal obesity.Materials and methods. The study included 96 men aged 58.9 ± 5.1 years: 80 men with angiographically verified atherosclerosis and class II–III angina pectoris and 16 men without atherosclerosis. Anthropometric parameters were measured in all patients, and their blood was taken on an empty stomach. The blood levels of adiponectin, leptin, resistin, adipsin, amylin, and metalloproteinases (MMPs) -1, -2, -3, -7, -9, -10, -12, -13 were determined by the multiplex analysis. Statistical processing of the results was carried out using the SPSS 13.0 software.Results. In patients with severe atherosclerosis, lipocalin, MMP-1, MMP-7, and MMP-12 levels were higher than in the control group. The blood concentration of adiponectin in patients with atherosclerosis was reduced. Inverse correlations were revealed between waist circumference and concentrations of MMP-1 and MMP-12, as well as between body mass index and MMP-1. A moderate direct relationship was revealed between resistin and MMP-2 and MMP-3; between amylin and MMP-9; between adiponectin and MMP-12; between leptin and MMP-7.Conclusion. The results obtained suggest a relationship between the level of damage markers and adipose tissue hormones, which lead to complications of cardiovascular diseases and explain the effect of obesity on atherosclerotic plaque destabilization.